Assessing the reuse of PICS bags in Jigawa, Kano, and Katsina States of northern Nigeria - Abdoulaye, Tahirou; Ayedun, B.; Musa, S.A.; Lowenberg-Deboer, J.; Baributsa, D. (International Institute of Tropical Agriculture, 2010)
In 2010, a survey was carried out in Jigawa, Kano and Katsina States to ascertain the level of reuse of the Purdue Improved Cowpea Storage (PICS) bags (technique for cowpea storage) among 2008 users. The PICS project has ecommended to farmers to reuse their PICS bags as long as they are not punctured. Survey results suggest that the majority of farmers (both demonstrators-DF [farmers that were used in the initial demonstrations] and ondemonstrators-NDF, those who bought PICS bags without participating in demonstrations) were reusing their PICS bags (66.2%, i.e., 90 respondents out of 136) for cowpea storage in 2009, while the remaining 33.8% (i.e., 46 respondents) reused their bags for other purposes such as storage of other crops, as bedding and roofing material, and given out to others. Among the reusers, 68.9% (62 respondents out of 90) were demonstrators and 31.1% (28 respondents) were nondemonstrators. To ascertain the determinants of reuse of PICS bags, a Logit model was fitted on the data with independent variables such as Farmer type, Age, Gender, Household size, Education, Membership of association, and quantity of cowpea harvested. The result on determinants of reuse of PICS for cowpea storage was significant at 1% level of probability. The result revealed, among others, that the probability of reusing the bag for cowpea storage statistically increased if the user was a demonstrator, an experienced farmer (age), male (gender), a member of a farmers’ association; the quantity of cowpea harvested aso affected reuse.